Effect of NaOH concentration to the growth of ZnO nanorod arrays / A. S. Ismail ...[et al.] - Ismail, A. S.; Mamat, M. H.; Shameem Banu, I. B.; Ahmad, W. R. W.; Md Sin, N. D.; Suriani, A. B.; Ahmad, M. K.; Zoolfakar, A. S.; Rusop, M. (UiTM Press, 2018)
Tin (Sn)-doped zinc oxide (ZnO) films were synthesized using sol-gel immersion method where different concentration of sodium hydroxide (NaOH) were used during the synthesis process. The structural, optical, and current-voltage (IV) characteristics of the films were investigated. From the FESEM images, it is observed that the density of the nanorods improved with the increment of NaOH concentrations. The average diameters of the nanorods reduced from 80 nm to 67 nm after the concentrations of NaOH were increased from 0 to 0.01 M. The optical measurement indicates that the synthesized films possessed good transmittance properties. 0.01 M of NaOH produced the highest bandgap energy of 3.26 eV compared to other films. In case of electrical properties measurement, 0.01 M NaOH produced the lowest resistance film. These results indicate that the addition of NaOH into acidic-based solution is crucial to control the growth of nanostructures.